Comparison of Structural Topography, Elemental Composition and Qualitative Analysis of two Indian mini-implants: A cross-sectional study - Bhawsar, Palash; Kallury, Amitabh; Jayade, Chetan; Balani, Rajesh Kumar; Bharti, Chandni (Orthodontic Journal of Nepal, 2022)
Objectives: This research was conducted to evaluate the surface topography, elemental composition and manufacturing defects of two brands of mini-implants commonly used in India. Clinical significance was derived based on the data of this research. Materials and methods: This research was conducted on 15 orthodontic mini-implants each from two brands commonly used in India. Scanning electron microscope imaging of the head, transmucosal neck, body, and tip was done to assess mini-implant topography and manufacturing defects (n=15/group). Analysis of elemental composition was done using an X-ray Powder Diffractor (n=1/group). Results: The results showed significant differences in both groups. Differences in structural topography of the implant body and tip were observed in both brands. Tip defects were detected in one brand. X-ray Powder Diffraction analyses revealed an alpha and alpha-beta titanium grain structure in both the groups. Conclusions: All the mini-implants tested were composed of titanium alloy. Significant differences were found in the surface area of the threaded parts. We conclude that differences in surface topography and presence of manufacturing defects impact the primary stability of the implants thereby influencing the efficacy of orthodontic anchorage.